Detection of mercury ions using silver telluride nanoparticles as a substrate and recognition element through surface-enhanced Raman scattering - Wang, Chia-Wei; Lin, Zong-Hong; Roy, Prathik; Chang, Huan-Tsung (Frontiers in Chemistry, 2013)
In this paper we unveil a new sensing strategy for sensitive and selective detection of Hg2+ through surface-enhanced Raman scattering (SERS) using Ag2Te nanoparticles (NPs) as a substrate and recognition element and rhodamine 6G (R6G) as a reporter. Ag2Te NPs prepared from tellurium dioxide and silver nitrate and hydrazine in aqueous solution containing sodium dodecyl sulfate at 90ºC with an average size of 26.8 ± 4.1 nm (100 counts) have strong SERS activity. The Ag2Te substrate provides strong SERS signals of R6G with an enhancement factor of 3.6 × 105 at 1360 cm-1, which is comparable to Ag NPs. After interaction of Ag2Te NPs with Hg2+, some HgTe NPs are formed, leading to decreases in the SERS signal of R6G, mainly because HgTe NPs relative to Ag2Te NPs have weaker SERS activity. Under optimum conditions, this SERS approach using Ag2Te as substrates is selective for the detection of Hg2+, with a limit of detection of 3 nM and linearity over 10-150 nM. The practicality of this approach has been validated for the determination of the concentrations of spiked Hg2+ in a pond water sample.